2013
DOI: 10.1016/j.juro.2013.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Co-Cultures Provide a New Tool to Probe Communication Between Adult Sensory Neurons and Urothelium

Abstract: Purpose Recent evidence suggests the urothelium functions as a sensory transducer of chemical, mechanical or thermal stimuli that signals to nerve terminals and other cells in the bladder wall. The cellular and molecular basis of neuro-urothelial communication is not easily studied in the intact bladder, which led us to establish a method of co-culturing dorsal root ganglion (DRG) sensory neurons and bladder urothelial cells. Materials and Methods Sensory neurons and urothelial cells obtained from DRG and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Cultured lumbar DRG (L3–L5) neurons were prepared using a published method (O'Mullane et al, 2013 ). After plating onto poly-L-ornithine (5 μg/ml)/laminin (5 μg/ml) coated coverslips for 1 h, DRG neurons were cultured for 24–30 h in fresh Neurobasal A/B27.…”
Section: Methodsmentioning
confidence: 99%
“…Cultured lumbar DRG (L3–L5) neurons were prepared using a published method (O'Mullane et al, 2013 ). After plating onto poly-L-ornithine (5 μg/ml)/laminin (5 μg/ml) coated coverslips for 1 h, DRG neurons were cultured for 24–30 h in fresh Neurobasal A/B27.…”
Section: Methodsmentioning
confidence: 99%
“…Fig 11 compares the normalized Ca 2+ transient evoked by application of 30 mM [K] o in bladder small DRG neurons generated in experiments [ 111 ] and by our model. Benham et.…”
Section: Resultsmentioning
confidence: 99%
“… (A) Comparison of normalized Ca 2+ transient obtained from bladder small DRG neurons experimentally (circles, Expt. Calcium Transient, [ 111 ] obtained from fluorescence studies) and our model (Solid line, Sim. Calcium Transient) by application of high [K] o (30 mM) for 50 seconds (indicated by bar).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial reports described TRPV1 expression and functional TRPV1 responses in isolated urothelial cells from mice , rats and humans . In contrast, an increasing number of groups have more recently reported the absence of TRPV1 expression and functional TRPV1 responses in guinea‐pig , mouse and human urothelial cells. Moreover, a recent approach using Trpv1 ‐reporter mice, suggested that TRPV1 expression was restricted to primary afferent neurones, with no detectable TRPV1 expression in urothelial cells .…”
Section: Trpv1mentioning
confidence: 99%